Primary spinal anaplastic ependymoma: A single-institute retrospective cohort and systematic review - Wu, Liang; Wang, Li’ao; Zou, Wanjing; Yang, Jun; Jia, Wenqing; Xu, Yulun (Frontiers in Oncology, 2023)
Objective: Primary spinal anaplastic ependymoma (PSAE) is an extremely rare disease. We aim to report the largest PSAE cohort, evaluate the treatments, and investigate the prognostic factors for progression-free survival (PFS). Methods: Clinical data collected from the authors’ institute and literature articles were pooled and described. Survival analysis and multivariable Cox regression analysis were performed to evaluate therapies and investigate prognostic factors for PFS. Results: Our cohort included 22 females and 16 males, with a median age of 33 years. PSAE developed mostly on cervical and cervicothoracic levels. The median length measured 3 segments. Half of PSAE were intramedullary. Pain was the most common symptom. The median duration of symptoms was 6 months. Neurological statuses were improved in 76% following treatments, whereas clinical tumor progression occurred in 41.7%. The estimated median progression-free survival was 132 months, and the estimated median survival was 192 months. The median Ki-67 index was 15%. Patients aged less than or equal to 25 experienced worse neurological statuses and more repeated progression. Age less than or equal to 25 (HR 10.312, 95%CI 1.535-69.260, p=0.016), gross total resection (HR 0.116, 95%CI 0.020-0.688, p=0.018), and radiotherapy (HR 0.084, 95%CI 0.009-0.804, p=0.032) are three prognostic factors for tumor progression. Conclusion: Tumor progression remains a big concern in the clinical course of PSAE. Being aged above 25, undergoing GTR, and accepting adjuvant radiotherapy put patients at lower risk for tumor progression. Younger patients might have worse neurological statuses compared with those aged over 25.